The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/nph.15462
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐tree nonstructural carbohydrate storage and seasonal dynamics in five temperate species

Abstract: Summary Despite the importance of nonstructural carbohydrates (NSC) for growth and survival in woody plants, we know little about whole‐tree NSC storage. The conventional theory suggests that NSC reserves will increase over the growing season and decrease over the dormant season. Here, we compare storage in five temperate tree species to determine the size and seasonal fluctuation of whole‐tree total NSC pools as well as the contribution of individual organs. NSC concentrations in the branches, stemwood, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
167
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(182 citation statements)
references
References 50 publications
(75 reference statements)
11
167
2
2
Order By: Relevance
“…5). The frequent sampling presented in this study allowed to clearly identify seasonal trends in the three studied species with reliable maxima and minima as advocated by recent work 37 . www.nature.com/scientificreports www.nature.com/scientificreports/ The total NSC concentrations in twigs varied dramatically throughout the year in the three species.…”
Section: Discussion Nsc Seasonal Trend Synchronism and Spatial Gradiementioning
confidence: 75%
See 1 more Smart Citation
“…5). The frequent sampling presented in this study allowed to clearly identify seasonal trends in the three studied species with reliable maxima and minima as advocated by recent work 37 . www.nature.com/scientificreports www.nature.com/scientificreports/ The total NSC concentrations in twigs varied dramatically throughout the year in the three species.…”
Section: Discussion Nsc Seasonal Trend Synchronism and Spatial Gradiementioning
confidence: 75%
“…NSC storage has seasonal fluctuations marked by the alternation between a favorable season with positive net carbon balance and a dormancy season when trees rely solely on stored NSC 10,12 . Seasonal NSC fluctuation has been reported for trees from various phylogenetic groups (gymnosperms and angiosperms), life habits (deciduous, evergreen), and biomes (Boreal, Temperate, Mediterranean and Tropical) in natural conditions 29,[31][32][33][34][35][36][37] . Despite the variability between tree species, NSC storage remains high throughout the year (never falling below 30% of the maximum NSC concentration).…”
mentioning
confidence: 99%
“…Spring girdling in Pinus taeda resulted in greater effects on stem respiration (e.g., increase above girdling and reduction below) than did autumn girdling (Maier et al, 2010). These seasonal differences corresponded to variations in stem soluble sugar and starch concentrations in girdled Pinus taeda (Maier et al, 2010), which was also the case for girdled Populus deltoides (Regier et al, 2010) and chilled Quercus robur , although it needs to be acknowledged that seasonal variations in nonstructural carbon concentrations are common for various species (Richardson et al, 2013;Furze et al, 2019). Overall, it is surprising, especially in locations with strong seasonality, that the timing of application in relation to reproductive and phenological cycles has not been unanimously observed to have strong effects on wood growth or tree mortality, especially given the importance of temperature for cambial re-activation (Oribe and Funada, 2017), hormonal signaling for cambial activity (Sorce et al, 2013), and the observed effects of treatment timing on respiration and nonstructural carbon remobilization.…”
Section: Collateral Effectsmentioning
confidence: 88%
“…Presumably, the increase of phloem sugar and starch concentrations above the girdling zone would eventually lead to increased leaf starch concentrations for passively loading pines. Interestingly, for Pinus taeda the changes in stem starch concentration were only significant when the girdling was performed in spring, as opposed to autumn (Maier et al, 2010), indicating that photosynthetic activity during the peak growing season, or underlying seasonal fluctuations in nonstructural carbohydrate reserves (Richardson et al, 2013;Furze et al, 2019), might drive this change. Despite the evidence for changes in starch remobilization, evidence for the relationship between starch accumulation and photosynthesis inhibition in trees is merely correlative at the moment, but leaf chlorosis due to starch accumulation is a common symptom of girdling in the horticultural experiments (Goren et al, 2004).…”
Section: Impacts Of Phloem Transport Manipulations On Carbon Dynamicsmentioning
confidence: 98%
“…For each organ, the stored NSC has been observed to be substantially different (Furze et al, 2018). Branches are the largest reservoir of NSC, and roots are considered as an organ that specializes in NSC storage (Kozlowski, 1992).…”
mentioning
confidence: 99%